Towards Transparent Markers - Xavier Natario Teixeira, Joao Marcelo; Burle, Alexandre de Queiroz; de Andrade Almeida, Arthur; de Gusmao Lafayette, Thiago Buarque; Ventura, Vinicius Lima; Carvalho, Vitor Mendes; Teichrieb, Veronica (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2021)
For many years, 2D fiducial markers played one of the most important roles in Augmented Reality (AR) solutions. As AR evolved, this type of marker gave place to markerless alternatives, supported by the increase in processing power of desktop and mobile platforms. Besides that, 2D fiducial markers are still used nowadays. In this work, we proposed to extend their capability by adding transparency to them. This brings different limitations on the marker construction process but on the other hand it enables new uses not possible before. Markers can now be used to manipulate virtual objects being viewed from both sides and they can also be stacked together and still be recognized. We demonstrate such new features with two different real-time samples together with an analysis regarding the main limitations of the solution, providing some application scenarios that could directly benefit from transparent markers.